Разработка метода поиска объектов интереса на карте на основе анализа пользовательских данных - Галаган, В. В. (ХНУРЕ, 2019)
The given work is devoted to the study of methods for finding the shortest path on the map, as well as the development of a hybrid method based on existing ones. The problem of analyzing various algorithms associated with graphs and finding a solution to finding the optimal path will be considered, taking into account the peculiarities of the process of distribution of communication network resources. The main goal is to increase the speed of the existing methods and increase the accuracy of the results